2017
DOI: 10.1051/0004-6361/201731798
|View full text |Cite
|
Sign up to set email alerts
|

The global meter-level shape model of comet 67P/Churyumov-Gerasimenko

Abstract: We performed a stereo-photogrammetric (SPG) analysis of more than 1500 Rosetta/OSIRIS NAC images of comet 67P/ChuryumovGerasimenko (67P). The images with pixel scales in the range 0.2−3.0 m/pixel were acquired between August 2014 and February 2016. We finally derived a global high-resolution 3D description of 67P's surface, the SPG SHAP7 shape model. It consists of about 44 million facets (1−1.5 m horizontal sampling) and a typical vertical accuracy at the decimeter scale. Although some images were taken after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 9 publications
0
70
0
Order By: Relevance
“…The effective spherical diameters, calculated from the best fit ellipsoidal dimensions in the second column, are presented in the third column and provide perhaps the best single number for the size of the object. The density for 67P is exceedingly well determined (16) and lies roughly in the middle of the ranges estimated for JFC nuclei. Due to the jetting force from cometary outgassing, the rotational periods of JFC nuclei change with time, so only approximate current values are listed for them.…”
Section: Supplementary Text Expected Impact Crater Morphologiesmentioning
confidence: 75%
See 1 more Smart Citation
“…The effective spherical diameters, calculated from the best fit ellipsoidal dimensions in the second column, are presented in the third column and provide perhaps the best single number for the size of the object. The density for 67P is exceedingly well determined (16) and lies roughly in the middle of the ranges estimated for JFC nuclei. Due to the jetting force from cometary outgassing, the rotational periods of JFC nuclei change with time, so only approximate current values are listed for them.…”
Section: Supplementary Text Expected Impact Crater Morphologiesmentioning
confidence: 75%
“…Comets 19P, 67P, and 103P appear to be highly elongated bilobate objects, suggesting the merger of two distinct bodies, as has been proposed for Arrokoth (1,18), though for comets it is also possible that thermal evolution has generated this shape (e.g., 60). Except for 67P, whose bulk density is 538 ± 1 kg m -3 (16), the densities of the other JFC nuclei are uncertain by a factor of two or more, but all are consistent with ~500 kg m -3 (61), which implies average bulk porosities of ~50-80%. Arrokoth's density is likely greater than 290 kg m -3 (see above), and thus at least consistent with those of JFC nuclei.…”
Section: Comparison To Jupiter Family Cometsmentioning
confidence: 95%
“…9 (top panel), along with a map identifying the different regions of the nucleus (bottom panel). The distribution of solar irradiance is calculated on a polyhedral shape model representing the nucleus of 67P with 499,902 facets (Preusker et al 2017). For each epoch, the Sun's position in the Cheops body-fixed frame of the comet (as defined in Preusker et al 2015) is derived from the reconstructed ephemeris and rotational status of 67P using the SPICE tool-kit (Acton 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Possible outliers are the cold classical Borasisi and the 2:1 resonant body 2002 WC 19 ; those may have higher densities but uncertainties are huge. For comparison, precise measurement of the 67P/Churyumov Gerasimenko nucleus by the Rosetta mission yields a density of 537.8±0.7 kg/m 3 , and a large porosity (70-80%, Sierks et al 2015;Pätzold et al 2016;Preusker et al 2017). Vilenius et al (2014) also found that the sizes of the binaries components for objects smaller than 400 km are not significantly different from each other.…”
Section: Ring Thermal Emissionmentioning
confidence: 97%